INSTALLING LINUX OS OVER NETWORK IN AREA OF ITCGH (USING,” KICKSTART”) - Habibi, Khan Mohammad; Rasooli, Abdul Qadeer; Wahedi, Nesar Ahmad (ZONAsi: Jurnal Sistem Informasi, 2023)
Here in this monoscript installing operating system over the network, you will commonly find four solutions ways for these four problems Such as Cost savings, centralization, timekeeping, and security which has always challenged IT centers in Afghanistan as well as in Ghor province. This search goal is an possabel OS placement concept for IT centers. Using one of the OS spread methods over a network called “Kickstart”. One of the most problematic obstacles against IT centers every day is IT centers' computers which are fundamental tools in many disciplines of study and work. In many cases, they are offered to users inside an open room to be used freely for their needs. ITCGh (Information Technology Center Ghor ) is one example. During my year at the university, it was possible to observe the technological dependence of a tool used to deploy OS all along with the computers. Kickstart is a well defined program we can work with this in the form of Command-line (CLI) and Graphical User Interface (GUI). It response the queries while OS installation. Finally, DHCP, TFTP, FTP, xinetd, and syslinux are the protocols that we need to configure in our Server System.